Effectiveness of Medical and Surgical Treatments in Managing Inferior Turbinate Hypertrophy: A Systematic Review - Iwan Setiawan Adji; Vania Qurratu Ain; Rizka Aretha Dewi; Aisyah Nabilah (Jurnal Ilmu Kedokteran, 2026)
Inferior turbinate hypertrophy is a major cause of chronic nasal obstruction and significantly reduces quality of life. Multiple treatment modalities are available, ranging from medical therapy to minimally invasive procedures and conventional surgery, yet their comparative clinical effectiveness remains unclear. This systematic review followed the PRISMA protocol. Literature searches were conducted in PubMed, SpringerLink, ScienceDirect, and Google Scholar. A total of 3,300 records were identified, and 27 studies met the inclusion criteria. Clinical outcomes were assessed using patient-reported symptom scales and quality-of-life instruments, including the Visual Analogue Scale, Nasal Obstruction Symptom Evaluation, and Sino-Nasal Outcome Test (SNOT-20/22). Overall, 25 of 27 studies (92.6%) reported clinically significant improvement in nasal obstruction symptoms. Surgical interventions demonstrated the most consistent effectiveness, with all surgical studies (100%) reporting significant symptom reduction and quality-of-life improvement, particularly with inferior turbinoplasty and microdebrider-assisted techniques. Minimally invasive modalities such as radiofrequency ablation and laser therapy were effective in 90% of studies, mainly providing faster early symptom relief with low complication rates. In contrast, medical therapy showed improvement in mild to moderate cases but was generally less durable and less effective compared to procedural interventions. Evidence suggests that surgical reduction, especially microdebrider-assisted turbinoplasty and inferior turbinoplasty, provides the most consistent and sustained clinical benefit in patients with inferior turbinate hypertrophy refractory to medication.